QADIMGI QANG' DAVLATINING HORIJIY MUALLIFLAR ASARLARIDA O‘RGANILISH TARIXSHUNOSLIGI - Normo'minov Dilbek Ilyos o'g'li, Ibragimov Anvar Sodiq o’g’li (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article provides information about the Ancient State of Kang. This article describes the location of this state, the time of its origin, the most prosperous period and its rulers. In addition, trade, relations with other countries, and the socio economic life of the Kan state are also covered.